2008
DOI: 10.1111/j.1365-2044.2008.05680.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of low dose plain solutions of local anaesthetic agents for spinal anaesthesia in the prone position: bupivacaine compared with levobupivacaine

Abstract: SummaryIn this study, we aimed to test the hypothesis that 1-ml plain solution of 0.5% bupivacaine or 0.5% levopubivacaine administered in a subarachnoid block can provide adequate anaesthesia and operating conditions for pilonidal cyst ⁄ sinus operations performed in the prone position. There were no significant differences between the two groups in terms of patient demographic data, duration of operation, patient-surgeon satisfaction, haemodynamic changes and side effects. There were no significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 17 publications
2
11
0
2
Order By: Relevance
“…As all of the groups received opioid, we found that onset and maximum cephalic spread times were similar among the groups, while maximum sensory block height was greater in group 10. The motor block was more intensive in groups that had a higher dose of local anesthetic, as expected since the lower incidence of complete motor block was related to the lower dose of local anesthetic used [24]. In addition, the epidural supplements may prolong motor and sensory block at the end of the procedure [21,25].…”
Section: Discussionmentioning
confidence: 53%
“…As all of the groups received opioid, we found that onset and maximum cephalic spread times were similar among the groups, while maximum sensory block height was greater in group 10. The motor block was more intensive in groups that had a higher dose of local anesthetic, as expected since the lower incidence of complete motor block was related to the lower dose of local anesthetic used [24]. In addition, the epidural supplements may prolong motor and sensory block at the end of the procedure [21,25].…”
Section: Discussionmentioning
confidence: 53%
“…In our study, spinal anesthesia was performed with the patient in the left lateral decubitus position, and after injection, patients turned to the supine position immediately, and then all patients were put into the prone position. In Cuvas's [6] study, which was also performed in the prone position, the characteristics of sensory and motor blocked were similar in the bupivacaine and levobupivacaine groups. But they used low- dose isobaric local anesthetic and spinal anesthesia was performed with the patient in sitting position and operations performed in the standard prone position.…”
Section: Discussionmentioning
confidence: 85%
“…Hyperbaric local anesthetic solutions are generally used in spinal anesthesia, but in the prone position, it may cause the spread of the local anesthetic solution in a cephalic direction and produce motor blockade in the anterior roots of the thoracic region, leading to ventilatory depression [6]. In the prone position, local anesthetic concentration in the anterior spinal segments increases over time and motor blockade also increases.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal block is associated with lower rate of side effects and better cost/benefit ratio than general anesthesia, and it is well accepted by patients 3 . Unlike 5 mg of isobaric solution (bupivacaine/levobupivacaine) that produces complete motor blockade in 15% of the patients 19 , the hypobaric solution (bupivacaine/lidocaine) does not cause the same; motor blockade was not observed in 90% of the patients. To conclude, spinal block with hypobaric bupivacaine (4.5 mg) or lidocaine (18 mg) was effective and safe in anorectal surgeries and preserved motor function.…”
Section: Discussionmentioning
confidence: 94%